La visita del Papa Benedicto XVI a Turquía: la Santa Sede ante la Sublime Puerta - Corral, Carlos; Abad, Gracia (UNISCI Discussion Papers, 2007)
From November, 28th to December, 1st 2006 Pope Benedict XVI paid a visit to Turkey, undertaking the fifth journey since he was elected in 2005. The visit, given the political and religious circumstances of the moment appeared full of symbolism and significance from the beginning. On this backdrop, the journey would be aimed at three main objectives: the pastoral mission, the ecumenical dialogue and the inter-religious dialogue and strongly marked by a burning question: religious freedom.
Keywords: Benedict XVI; Turkey; Ecumenism; Inter-Religious Dialogue; Religious Freedom